Oral health-related quality of life of older patients attending a government dental hospital in India - Abhishek Mehta; Murali Govind; Jonathan Broadbent (Wolters Kluwer Medknow Publications, 2020)
Background: Caries, periodontal disease, and tooth loss affect the quality of life of older people. There is a need for research on the oral health of older Indians. Aim: To assess oral health and its impact on the quality of life of older adults visiting a government dental hospital in New Delhi, India. Methods: A cross-sectional study was conducted on a convenience sample of 255 older adults (above 60 years). Dental caries experience was quantified by a count of teeth that were carious, restored, and missing due to caries (Decayed, Missing, and Filled Teeth), while periodontal health was quantified using the Community Periodontal Index. Oral health-related quality of life (OHRQoL) was assessed using a Hindi version of the General Oral Health Assessment Index (GOHAI). Results: The mean GOHAI score was 24.2 (SD 4.3). More than half of the study participants had untreated caries and periodontal problems. Regression analysis showed that OHRQoL scores were associated with age, female sex, poorer educational level, and number of missing teeth in the sample population. Conclusion: Unmet need for dental treatment was prevalent and affects the quality of life of older Indians. Self-care and the use of preventive dental services should be promoted, while access to treatment services should be improved for this population group.